Low flucloxacillin concentrations in a patient with central nervous system infection: the need for plasma and cerebrospinal fluid drug monitoring in the ICU - Abdul Aziz, Mohd. Hafiz; McDonald, Craig; McWhinney, Brett; Ungerer , Jacobus P.; Lipman, Jeffrey; Roberts, Jason A. (Sage Publishing, 2014)
Objective:To report the difficulty in achieving and maintaining target antibiotic exposure in critically ill patients with deepseeded infections. Case Summary: We present a case of a 36-year-old man who was admitted to the intensive care unit with diffuse central nervous system and peripheral methicillin-sensitive Staphylococcus aureus infection (minimum inhibitory concentration; MIC, 1 μg/mL). Owing to the complicated nature of the infection, sequential concentrations of free flucloxacillin were measured in plasma and cerebrospinal fluid (CSF) and used to direct antibiotic dosing. Unsurprisingly, the trough plasma concentrations of flucloxacillin were below the MIC (0.2-0.4 μg/mL), and the corresponding CSF concentrations were undetectable (<0.1 μg/mL) with standard intermittent bolus dosing of 2 g every 4 hours. By administering flucloxacillin by continuous infusion (CI) and increasing the dose to 20 g daily, the plasma (2.2-5.7 μg/mL) and CSF (0.1 μg/mL) levels were increased, albeit lower than the predefined targets (plasma, 40 μg/mL; CSF, 4 μg/mL). Discussion: The presence of physiological changes associated with critical illness—namely, hypoalbuminemia and augmented renal clearance—may significantly alter antibiotic pharmacokinetics, and this phenomenon may lead to suboptimal antibiotic exposure if they are not accounted for. This case also highlights the value of applying CI in such patient groups and demonstrates the significance of monitoring plasma and CSF drug concentrations in optimizing antibiotic delivery. Conclusions: Future research should aim to evaluate the utility of such drug monitoring with regard to patient outcomes and cost-effectiveness.